The Gut Microbial Profile of Preclinical Crohn's Disease Is Similar to That of Healthy Controls. Issue 11 (27th April 2020) - Kuballa, Anna; Geraci, Marco; Johnston, Meredith; Sorrentino, Dario
Abstract: Background and Aims: It is unclear whether microbial dysbiosis plays an etiologic role in Crohn's disease (CD) or is the result of protracted inflammation. Here, we test the hypothesis that dysbiosis predates clinical CD in asymptomatic first-degree relatives (FDRs) of CD patients: normal (FDR1), with borderline inflammation (FDR2), and with frank, very early inflammation (FDR3). Methods: The gut microbial diversity was tested in ileocecal biopsies through next generation sequencing of the 16S rRNA gene in 10 healthy controls (HCs), 22 patients with active, untreated CD, and 25 FDRs (9 FDR1; 12 FDR2; 4 FDR3). The metagenomic functions of 41 microbiome-related processes were inferred by Phylogenetic Investigation of Communities by Reconstruction of Unobserved States (PICRUSt) analysis. Results: Compared with HCs, alpha diversity in CD patients was decreased, with an observed decrease in Faecalibacterium prausnitzii and increase in Bacteroides fragilis . In FDRs, microbial diversity was unchanged compared with HCs. In Operational Taxonomic Units and PICRUSt Principal coordinates and component analyses, the ellipse centroid of FDRs was diagonally opposed to that of CD patients, but close to the HC centroid. In both analyses, statistically significant differences in terms of beta diversity were found between CD and HC but not between FDR and HC. Conclusions: In FDRs (including FDR3—who bear preclinical/biologic onset disease), we found that the microbial profile is remarkably similar to HC. If confirmed in larger studies, this finding suggests that clinical CD-associated dysbiosis could result from the changed microenvironment due to disease evolution over time.